Performance of a Two-Week Rehabilitation Improves Motor Function in Inpatients with Progressive Supranuclear Palsy: A Pre–Post Study - Naomi Matsuda; Yasuyuki Takamatsu; Makoto Sawada; Ikuko Aiba (Brain Sciences)
Background: Progressive supranuclear palsy (PSP) is characterized by early postural instability and gait dysfunction, with frequent falls. Rehabilitation is an important therapeutic approach for motor dysfunction in patients with PSP. However, no conclusions have yet been drawn regarding the beneficial effects of rehabilitation in PSP, including the optimal duration of rehabilitation and differences in treatment effects among PSP subtypes. Herein, we investigated the effects of short-term rehabilitation and separately analyzed the effects on patients with PSP-Richardson’s syndrome (RS) and PSP-progressive gait freezing (PGF). Methods: The participants underwent several therapeutic exercise programs individualized for each participant, performed over 2 weeks. Analysis was performed on 25 patients with PSP-RS and eight with PSP-PGF. Results: Short-term rehabilitation improved the Berg Balance Scale score in both the PSP-RS and PSP-PGF groups, step length on the symptom-dominant side in PSP-RS, the coefficient of variation of step length on the symptom-dominant side, and the stance phase of the Symmetry Index in PSP-PGF. Conclusions: Overall, this 2-week short-term rehabilitation intervention was shown to have beneficial effects on balance in patients with PSP-RS and PSP-PGF.